Run silent, run deep [videorecording (DVD)] - Gable, Clark, 1901-1960; Lancaster, Burt, 1913-1994; Warden, Jack; Wise, Robert, 1914-2005; Beach, Edward L. (Edward Latimer), 1918-2002 (MGM DVD., 1999)
The realities of submarine warfare during World War II in the Pacific is centered around two submarine officers who are destined to clash with each other from the first moment they meet.